Zero-carbon balance: The case of HouseZero. (January 2022) - Grinham, Jonathan; Fjeldheim, Henning; Yan, Bin; Helge, Tor Dokka; Edwards, Kristian; Hegli, Tine; Malkawi, Ali
Abstract: In response to establishing net-zero carbon emissions buildings and the need to make transparent the methods used for calculating the embodied CO2e emissions of these projects, this paper presents a case study of one project. The paper first outlines the life cycle assessment method used, including system boundaries, data availability, scenarios, assumptions, and uncertainties. Whole building life cycle assessment results show normalized embodied CO2e emissions of 488 kg CO2e/m 2 . If system boundaries are aligned to current benchmarking studies, this value is 233 kg CO2e/m 2 . When considering system boundaries, the results show that upwards of 42% of the project's CO2e emissions are generated by technical systems beyond those accounted for in contemporary life cycle assessment studies. The paper also provides a method to calculate the building's carbon balance over its 100-year service life based on multiple future energy supply CO2-intensity scenarios. The results show that the building can achieve carbon balance under conservative scenarios when a zero-carbon emissions energy supply is not achieved by 2050. The results illustrate the importance of transparency when declaring zero-carbon balance in a project. The uncertainties of such a declaration are also discussed, along with the relationship of the building's operational and embodied carbon emissions. Highlights: A transparent whole building lifecycle assessment study is provided. Renewable and MEP systems have a significant impact on lifecycle carbon emissions. Zero-carbon balance can be achieved; results are sensitive to study scenarios and scope. Building design, materials selection, and embodied carbon benchmarking are discussed.